2011
DOI: 10.1108/01443331111177878
|View full text |Cite
|
Sign up to set email alerts
|

Informal economy, informal state: the case of Uzbekistan

Abstract: PurposeIn the Soviet Union, the official command structure for economic production and distribution gave rise to, and depended upon, what has been described as a “shadow” economy. In the post‐socialist context, the unregulated, often extra‐legal activities of production and exchange, encompassing the survival strategies of the poor, the emergence of post‐socialist “Mafias”, and much entrepreneurial activity, has been described using the concept of the “informal economy”.Design/methodology/approachThe paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…Thus, the way the driver distinguishes between 'good' and 'bad' bribery indicates the existence of dual morality in bribery and reveals the multifaceted meaning and morality of informal transactions in Uzbekistan. A similar situation has also been described in Rasanayagam's (2011) study in which he, through an ethnographic case study of a local teacher in Uzbekistan, showed the clashes between social norms and law where the local teacher believed that a 'little corruption' does not hurt anyone.…”
Section: Authors' Commentssupporting
confidence: 64%
See 3 more Smart Citations
“…Thus, the way the driver distinguishes between 'good' and 'bad' bribery indicates the existence of dual morality in bribery and reveals the multifaceted meaning and morality of informal transactions in Uzbekistan. A similar situation has also been described in Rasanayagam's (2011) study in which he, through an ethnographic case study of a local teacher in Uzbekistan, showed the clashes between social norms and law where the local teacher believed that a 'little corruption' does not hurt anyone.…”
Section: Authors' Commentssupporting
confidence: 64%
“…Anthropological studies have demonstrated the existence of local perceptions of moral codes and values of informal transactions that significantly differ from Western morality and standards (Abramson 2000;Werner 2000;Kurkchiyan 2000;Humphrey 2002Humphrey , 2012Wanner 2005;Sneath 2006;Markowitz 2008;Polese 2008;Ledeneva 2009;Rasanayagam 2011;Urinboyev 2011b;Urinboyev and Svensson 2013). This literature is based upon a theoretical understanding of money, gifts, and the morality of exchange (Mauss 1924;Parry and Bloch 1989;Thomas 1991), as well as empirical studies concerned with different kinds of transactions between citizens and state officials.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In other words, such incomes and other rents associated with a post are collected as returns from an 'investment' in public office (Engvall 2014(Engvall , 2015. It is within this system of public posts for sale that exploitive activities of officials occur (Humphery and Sneath 2004;Rasanayagam 2011).…”
Section: Central Asian Surveymentioning
confidence: 98%